Insights into the Maturation of Hyperthermophilic Pyrolysin and the Roles of Its N-Terminal Propeptide and Long C-Terminal Extension - Dai, Zheng (American Society for Microbiology, 2012)
Pyrolysin-like proteases from hyperthermophiles are characterized by large insertions and long C-terminal extensions (CTEs). However, little is known about the roles of these extra structural elements or the maturation of these enzymes. Here, the recombinant proform of Pyrococcus furiosus pyrolysin (Pls) and several N- and C-terminal deletion mutants were successfully expressed in Escherichia coli. Pls was converted to mature enzyme (mPls) at high temperatures via autoprocessing of both the N-terminal propeptide and the C-terminal portion of the long CTE, indicating that the long CTE actually consists of the C-terminal propeptide and the C-terminal extension (CTEm), which remains attached to the catalytic domain in the mature enzyme. Although the N-terminal propeptide deletion mutant PlsΔN displayed weak activity, this mutant was highly susceptible to autoproteolysis and/or thermogenic hydrolysis. The N-terminal propeptide acts as an intramolecular chaperone to assist the folding of pyrolysin into its thermostable conformation. In contrast, the C-terminal propeptide deletion mutant PlsΔC199 was converted to a mature form (mPlsΔC199), which is the same size as but less stable than mPls, suggesting that the C-terminal propeptide is not essential for folding but is important for pyrolysin hyperthermostability. Characterization of the full-length (mPls) and CTEm deletion (mPlsΔC740) mature forms demonstrated that CTEm not only confers additional stability to the enzyme but also improves its catalytic efficiency for both proteineous and small synthetic peptide substrates. Our results may provide important clues about the roles of propeptides and CTEs in the adaptation of hyperthermophilic proteases to hyperthermal environments.